Lineage plasticity and treatment resistance in prostate cancer: the intersection of genetics, epigenetics, and evolution - Imamura, Jarrell; Ganguly, Shinjini; Muskara, Andrew; Liao, Ross S.; Nguyen, Jane K.; Weight, Christopher; Wee, Christopher E.; Gupta, Shilpa; Mian, Omar Y. (Frontiers in Endocrinology, 2023)
Androgen deprivation therapy is a cornerstone of treatment for advanced prostate cancer, and the development of castrate-resistant prostate cancer (CRPC) is the primary driver of prostate cancer-related mortality. While CRPC typically develops through a gain in androgen receptor (AR) signaling, a subset of CRPC will lose reliance on AR. This process involves genetic, epigenetic, and hormonal changes that promote cellular plasticity, leading to AR-indifferent disease, with neuroendocrine prostate cancer (NEPC) being the quintessential example. NEPC is enriched following treatment with second-generation anti-androgens and exhibits resistance to endocrine therapy. Loss of RB1, TP53, and PTEN expression, and amplification of MYCN and AURKA, appear to be key drivers for NEPC differentiation. Epigenetic modifications also play an important role in the switch to the neuroendocrine phenotype. DNA methylation of specific gene promoters can regulate lineage commitment and differentiation. Histone methylation can suppress AR expression and promote neuroendocrine-specific gene expression. Emerging data suggest that EZH2 is a key regulator of this epigenetic rewiring. Several mechanisms drive AR-dependent castration resistance, notably AR splice variant expression, expression of the adrenal-permissive 3βHSD1 allele, and glucocorticoid receptor expression. Aberrant epigenetic regulation also drives radioresistance in prostate cancer by altering the expression of DNA repair- and cell cycle-related genes. Novel therapies are currently being developed to target these diverse genetic, epigenetic, and hormonal mechanisms promoting lineage plasticity-driven CRPC.